ANALISIS MISKONSEPSI MENGGUNAKAN TES DIAGNOSA THREE-TIER MULTIPLE CHOICE PADA MATERI STOIKIOMETRI - Lestari, Etika Ayu; Harjito, Harjito; Susilaningsih, Endang; Wijayati, Nanik (Jurnal Inovasi Pendidikan Kimia, 2021)
This study aims to analyze the profile of students' misconceptions on stoichiometric material and to find out the findings obtained from the misconception analysis. This research method is a mixed method with a sequential explanatory design. Quantitative data collection methods using test and questionnaire methods. Qualitative data method with interview method. The total misconception profile on stoichiometric material was 44.6%. The profile of misconceptions based on the achievement of the highest concept understanding indicator was 65%. The concepts that cause chemical misconceptions of stoichiometric competence in students include the basic laws of chemistry, molar mass, molar volume, number of particles, limiting reagents and empirical formulas. Factors that can cause misconceptions in students found by researchers are situations that are less conducive, lack of student interest in learning chemistry, learning methods that are not correct, lack of courage to ask questions, low student motivation.